Relational Collusion in the Colombian Electricity Market - Mario Bernasconi; Miguel Espinosa; Rocco Macchiavello; Carlos Suarez (Center for Economic Studies and ifo Institute (CESifo), 2023)
Under collusion, firms deviate from current profit maximization in anticipation of future rewards. As current profit maximization places little restrictions on firms' pricing behaviour, collusive conduct is hard to infer. We show that bids from certain firms in the Colombian wholesale electricity market collapsed immediately after the announcement, and before the implementation, of a reform that potentially made collusion harder to sustain. After ruling out confounders, we uncover how the cartel functioned and how firms may have communicated. Calibrating the dynamic enforcement constraint confirms that collusion was sustainable before, but not after, the reform. The conclusions discuss policy implications.
Keywords: 330; Strommarkt; Wettbewerbsbeschränkung; Regulierung; Kolumbien